Organogênese e características morfoanatômicas de pinhão-manso - Nunes, Claudinéia Ferreira (2010)
Through the need for production of inputs for biofuels and the expansion of knowledge of the specie, this study aimed to analyze the germination of zygotic embryos and the in vitro organogenesis, as well as to characterize morphologically, leaves and callus of physic nut. The results indicate that the IVG is greater in 30 ºC. Increased number of normal seedlings is obtained in white light and seedling more developed in the absence of light. Its development of the specie studied occurs in the absence and presence of light, characterizing it as neutral photoblastic. Can be characterized as an amphihypostomatic specie, with greater presence of stomata on the abaxial surface, independent of lighting conditions or temperature. The MS medium with half concentration of salt favors the formation of callus. The intensity of callus staining and the explant source are parameters to be used in evaluating and choosing a treatment aiming organogenesis. The BAP induces higher levels of buds and shoots formation and, the bud regeneration using as source of explant cotyledonary leaves of in vitro seedlings, is desirable for the morphogenetic response. The absence of coconut water in the culture medium favors the multiplication of shoots. The use of plastic film, followed by the polypropylene cap with filter has a positive effect on the induction of organogenesis in explants of physic nut. The characteristics of buds formation on the surface of explants of physic nut can be used as descriptors of organogenesis, and the structures formed, on nutrient medium with lower concentrations of coconut water and the use of sealing that allow the minimum of gas exchange with the external environment, are satisfactory. It is recommended concentrations between 50 and 100% of KNO3 and NH4NO3 in the MS medium because it favors the induction of responsive callus with formation of early plants. The highest number of shoots is obtained at 60 days of culture with concentration of 150% to NH4NO3 and up to 100% to KNO3, compared to the standard concentration of MS medium.